IDEOLOGI, KEYAKINAN, DOKTRIN DAN BID’AH KHAWARIJ: Kajian Teologi Khawarij Zaman Modern - Sukring, Sukring (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Islam is a religion of balance and moderation, Muslim are supposedly the people of the middle or the neutral people. But in fact, this word means not to be excessive (moderate). Its modesty appears in doctrine and morals. That is the main characteristic of Islam. Those who are far away from moderation have indeed moved away from the spirit of Islam. Throughout ages there have been always extreme groups. Consequently, they will be shunned by people, although they outwardly practice good deeds and are devout. In this case, the most obviously extreme group was the Khawarij. Killing Muslims deemed valid by the Khawarij. Even today Khawarij still uses the name of Islam and raised slogans to establish a divine order. However, all of their actions and steps actually violate the teachings of Islam. Khawarij passed through indelible traces in the history. Nevertheless, Nowadays, there are groups showing up again in the world and in the new paradigm of Khawarij by murder,rebellion in a legitimate government, and terrorism. The scholars indicate they are modern Khawarij.Islam adalah agama seimbang dan moderat, sebagai umat pertengahan, perantara, atau bangsa yang netral. Namun faktanya, kata ini bermakna tidak berlebih-lebihan (moderat). Kesederhanannya tampak dalam doktrin dan akhlak. Itulah ciri utama dari Islam. Mereka yang menjauhkan diri dari sikap moderat telah menjauh dari semangat Islam yang sebernarnya. Sepanjang zaman akan selalu muncu kelompok-kelompok yang berhaluan ekstrim. Sebagai konsekwensi, mereka akan dijauhi umat, meski secara lahiriah menampilkan amalan Islam dan taat dalam beragama. Dalam hal ini kelompok yang paling kentara adalah Khawarij. Membunuh orang Muslim dianggap sah oleh Khawarij. Bahkan hari ini Khawarij menggunakan nama Islam dan mengangkat slogan-slogan untuk membangun tatanan Ilahi. Akan tetapi, semua tindakan dan langkah mereka sejatinya merupakan pelanggaran terhadap ajaran Islam. Ketika para pendukung Khawarij tidak memiliki dalil yang sah untuk tindakan mereka. Aliran Khawarij telah berlalu dengan jejak yang tak terhapuskan dalam sejarah. Namun dalam perkembangan zaman, kelompok ini mulai kembali dalam pentas dunia, dalam paradigma baru dengan melakukan pembunuhan, pemberontakan pada pemerintah yang sah, dan terorisme. Para ulama mengindikasikan mereka adalah kelompok Khawarij zaman modern